Reproductive Ecology of the Chilean Round Ray (Urotrygon chilensis, Günther, 1872) in the Southern Gulf of California - Carlos J. Alvarez-Fuentes; Javier Tovar-Ávila; Jorge Payan-Alejo; Darío A. Chávez-Arrenquín; Isaias H. Salgado-Ugarte; Felipe Amezcua (Fishes, 2023)
The Chilean round ray (Urotrygon chilensis, Günther, 1872) is commonly caught as bycatch in the Mexican Pacific, but changes in its reproductive ecology as a consequence of fishery effects have never been investigated. In this work, the reproductive ecology of this species was determined in the Southern Gulf of California (SGC). Total length (TL) ranged from 11.4 to 51.6 cm, and females were larger than males. Size at maturity (TL50) was estimated at 27.5 cm for females and 25.3 cm for males. The seasonal variation of mature individuals, the presence of pregnant females, the mean oocyte size, the size of embryos and the smallest free-living specimens along the year suggest the existence of two reproductive periods during the year in the SGC, and the size of birth was estimated to be 11.2 to 15.6 cm TL. The average fecundity was 2.14 embryos. Spatial variations detected in size at maturity, fecundity, and reproductive cycle along the Mexican Pacific coast suggest the presence of separated populations. Some of these differences could be related to differences in maximum size attained in each region, though fishing pressure and environmental factors could have an important role, too.